Solid-state white light-emitting electrochemical cells based on scattering red color conversion layers. Issue 48 (23rd November 2015) - Lin, Guan-Rung; Cheng, Jing-Rong; Wang, Chi-Wei; Sarma, Monima; Chen, Hsiao-Fan; Su, Hai-Ching; Chang, Chih-Hao; Wong, Ken-Tsung
Abstract : Efficient white LECs based on recycling the trapped EL in waveguide and substrate mode. Abstract : Solid-state white light-emitting electrochemical cells (LECs) based on ionic transition metal complexes are capable of generating efficient white electroluminescence (EL). Recently, blue-emitting LECs combined with embedded red color conversion layers (CCLs), which were inserted between indium tin oxide (ITO) and a glass substrate, have been reported to offer an external quantum efficiency (EQE) >12%. However, the output spectrum of EL from such white LECs changed with time due to the altered microcavity effect when the recombination zone was moving. Furthermore, the device efficiency should be further improved to realize practical applications. In this work, TiO2 nanoparticles (NPs) of two sizes are incorporated into red CCLs to improve device performance. Large NPs (250 nm) can scatter and redirect the light passing through red CCLs and further enhance the extracted light. Small NPs (25 nm) increase the refractive index of red CCLs and raise the amount of light intensity in the evanescent tail of the waveguide mode near the ITO layer. Therefore, more trapped light in the evanescent tail of the waveguide mode can be recycled to the external mode by scattering. The peak EQE and power efficiency of white LECs employing scattering red CCLs reach 20.0% and 39.5 lm W −1, respectively. Furthermore, with scattering NPs to average the EL in different directions, white EL is almost invariant with time. These results show that blue-emitting LECs combined with scattering red CCLs would be effective to provide efficient and stable white EL.